Enhancing compression ignition engine efficiency and reducing noise emissions: The impact of nanoparticle enhanced biodiesel blends - M. Anish; J.R. Deepak; Jayant Giri; Mohammed Rafi Shaik; M. Sangeetha; V. Jayaprakash; T. Sathish (Ain Shams Engineering Journal, 2025)
This study explores the potential of titanium oxide (TiO2) nanoparticles as additives in internal combustion engines, specifically with a CIB30(Calophyllum Inophyllum biodiesel) fuel blend comprising 30 % Calophyllum Inophyllum biodiesel and 70 % diesel. Employing ultrasonic treatment, the CIB30 mix was infused with 50 ppm of TiO2 nanoparticles. The investigation was conducted on a single-cylinder diesel engine running at a consistent speed of 1300 revolutions per minute. The results demonstrate enhanced brake-specific fuel consumption (BSFC) for both the DF70CIB30 and DF67CIB30TiO2 blends, further exhibiting substantial improvement. Notably, DF67CIB30TiO2 showcased a remarkable 4.92 % increase in brake thermal efficiency (BTE) over pure diesel. The incorporation of nanoparticles effectively lowered combustible noise by moderating the rate at which combustion pressure increased. Additionally, noise emissions were diminished when utilizing diesel blends as opposed to Natural diesel. These findings suggest that both DF70CIB30 and DF67CIB30TiO2 blends can be seamlessly integrated into diesel engines, with the latter demonstrating superior performance.